The Pattern of Microorganism on Adult Acute Leukemia PatientsDuring Bacterial Surveillance and Febrile Neutropenia at CiptoMangunkusumo Hospital - Sukrisman, Lugyanti (UI Scholars Hub, 2021)
Introduction. The standard intensive chemotherapy in acute leukemia patients will cause severe neutropenia and infection (febrile neutropenia) with high fatality rate. The availability of accurate data on causative pathogens is essential to the appropriate selection of empirical therapy and usually obtained from bacterial surveillance. This study was intended to evaluate bacterial pathogens found on surveillance and during febrile neutropenia in acute leukemia patients undergoing chemotherapy at Cipto Mangunkusumo Hospital and to provide information for antimicrobial policy in the hospital. Methods. A retrospective study from data of bacterial surveillance of acute leukemia patients undergoing chemotherapy during 2008-2010 in isolation room for acute leukemia patients at 8th floor of ‘Gedung A’ Cipto Mangunkusumo Hospital, Jakarta. The isolates for surveillance data were obtained from cultures from feces culture, nasal and throat swab, preputium swab and other sites (urine, sputum, skin infection - as indicated) from acute leukemia patients before and during intensive chemotherapy. Blood sample for blood culture was collected from central venous catheter and peripheral veins using Bactec during febrile neutropenia, and the other specimens (swab, urine, feces cultures) were collected according to the standard laboratory procedure. All specimens were collected by nurses in isolation room and bacterial cultures were performed at microbiology division of Clinical Pathology Department Cipto Mangunkusumo Hospital. Results. There were 1,127 isolates of acute leukemia patients (acute myeloid leukemia - AML or acute lymphocytic leukemia - ALL) that could be analyzed. Gram positive bacteria was significantly higher than gram negative bacteria from all cultures, from respiratory tract (514 out of 675 isolates; 76.1%) and blood culture (Staphylococcus epidermidis and Streptococcus anhemolyticus – 81 out of 103 isolates; 78.7%). Regarding bacterial surveillance in colon, only 8 out of 45 E. coli isolates from feces can be analyzed for sensitivity to ciprofloxacin/cotrimoxazole and the other 37 isolates were sensitive to other antimicrobials that not commonly used for gut decontamination in acute leukemia. The sensitivity pattern of the other isolates could not be analyzed to the antibiotics recommended for the management of febrile neutropenia due to wide range of antibiotics tested. Conclusion. From 1,127 isolates found among acute leukemia patients undergoing intensive chemotherapy at Cipto Mangunkusumo Hospital, it was found that gram positive was the most common bacteria found on upper respiratory tract from bacterial surveillance and from blood culture during febrile neutropenia